2017
DOI: 10.1007/s10508-016-0934-9
|View full text |Cite
|
Sign up to set email alerts
|

Diminishing Perceived Threat of AIDS and Increasing Sexual Risks of HIV Among Men Who Have Sex with Men, 1997–2015

Abstract: Community-wide awareness that ART provides protection against HIV has the potential to increase perceived safety and thereby increase condomless anal sex among men who have sex with men (MSM). Furthermore, reductions in condom use can increase exposure to sexually transmitted infections, which in turn can reduce the protective effects of ART on HIV transmission. The current study extends previous community-based behavioral surveillance research on beliefs regarding use of ART for HIV prevention and sexual prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 40 publications
1
16
0
2
Order By: Relevance
“…Underestimation of HIV risk has been reported as a significant predictor of both CAS and underutilization of HIV testing ( Golub & Gamarel, 2013 ; Stephenson, White, Darbes, Hoff, & Sullivan, 2015 ; White & Stephenson, 2016 ). HIV risk perception, particularly among young MSM, may be declining, partly due to “treatment optimism,” the awareness that antiretroviral treatments are highly effective in reducing HIV viremia ( Huebner, Rebchook, & Kegeles, 2004 ), along with the introduction of pre-exposure prophylaxis (PrEP), the use of antiretroviral medications among HIV to lower risk of HIV infection ( Chen, 2013 ; Kalichman et al, 2017 ). Studies have identified increases in condomless sex and higher rates of sexually transmitted infection among PrEP users, suggesting a potential association between prevention optimism and risk compensation related to PrEP ( Holt & Murphy, 2017 ; Traeger et al, 2018 ).…”
mentioning
confidence: 99%
“…Underestimation of HIV risk has been reported as a significant predictor of both CAS and underutilization of HIV testing ( Golub & Gamarel, 2013 ; Stephenson, White, Darbes, Hoff, & Sullivan, 2015 ; White & Stephenson, 2016 ). HIV risk perception, particularly among young MSM, may be declining, partly due to “treatment optimism,” the awareness that antiretroviral treatments are highly effective in reducing HIV viremia ( Huebner, Rebchook, & Kegeles, 2004 ), along with the introduction of pre-exposure prophylaxis (PrEP), the use of antiretroviral medications among HIV to lower risk of HIV infection ( Chen, 2013 ; Kalichman et al, 2017 ). Studies have identified increases in condomless sex and higher rates of sexually transmitted infection among PrEP users, suggesting a potential association between prevention optimism and risk compensation related to PrEP ( Holt & Murphy, 2017 ; Traeger et al, 2018 ).…”
mentioning
confidence: 99%
“…In our study, although HIV-positive females who were aware of their serostatus were more likely to report condom use by their male partners at their first visit, their sexual behavior did not change throughout Aristotle. This could be explained perhaps by the fact that PWID who were informed of their infection and initiated antiretroviral treatment developed a perception of safety due to treatment receipt and thereby increased condomless sex [51,52] despite counseling. Generally, condom use is remarkably low in stable relationships as opposed in commercial or casual sexual encounters, where is typically high [53,54].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has found that 30.2% of HIV transmissions per year are attributable to undiagnosed individuals living with HIV (Skarbinski, et al, 2015). Importantly, among a community-based sample of MSM, a recent study found that an increased belief that HIV treatment reduces transmission risk coincided with increased rates of CAS (Kalichman et al, 2017). In an age when ART is at the center of HIV prevention, such findings suggest a potentially problematic belief in treatment optimism and perceived lower infectivity among those who may not be virally suppressed.…”
Section: Discussionmentioning
confidence: 99%